2022
DOI: 10.48101/ujms.v127.8211
|View full text |Cite
|
Sign up to set email alerts
|

Endocan as a potential marker in diagnosis and predicting disease severity in COVID-19 patients: a promising biomarker for patients with false-negative RT-PCR

Abstract: Background: Endothelial-specific molecule 1 (endocan) has emerged as an inflammatory biomarker in recent years. The purpose of this study was to investigate the diagnostic value of serum endocan levels in the prediction of COVID-19 disease among patients with a false-negative reverse transcription polymerase change reaction (RT-PCR) test, and also to determine its correlation with the clinical severity of the disease. Methods: Thirty patients with positive RT-PCR results and 30 with false-negative RT-PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…Serum endocan levels showed significant changes in many acute and chronic conditions [ 14 , 15 ]. The present study found significantly higher endocan levels in patients' groups as compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Serum endocan levels showed significant changes in many acute and chronic conditions [ 14 , 15 ]. The present study found significantly higher endocan levels in patients' groups as compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Thromboinflammation, endotheliopathy and coagulopathy are frequent in severe COVID-19 [ 18 ], and thrombotic events are associated with worse prognoses in COVID-19 [ 19 ]. Very recently, several studies reported on potential interest in serum endocan as a potential marker in the diagnosis and prediction of disease severity in COVID-19 [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ], and most of them also mentioned the importance of this marker’s connection with thrombosis. However, none of them specifically focused on the potential role of endocan in identifying thrombotic injury in COVID-19, nor investigate the mechanistic importance of endocan in thromboinflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, 48 articles were excluded due to various reasons, while one was added by reference searching, as described in Figure 1. Finally, eight studies, [11][12][13][14][15][16][17][18] including 686 cases, were included in the systematic review. A detailed flowchart of the search and selection process is shown in Figure 1.…”
Section: Literature Search and Characteristics Of Included Studiesmentioning
confidence: 99%
“…The mean age of participants was 60.1 ± 14.0 years, and 62.9% were male. Four studies 11,12,15,18 measured endocan in plasma, and the other four 13,14,16,17 measured serum endocan levels. Half of the studies were conducted in Turkey 13,14,16,17 and three in France.…”
Section: Literature Search and Characteristics Of Included Studiesmentioning
confidence: 99%